Innovation of Shear Connectors in Slim Floor Beam Construction - Mohamed S. Majdub; Shahrizan Baharom; Ahmed W. Al Zand; Azrul A. Mutalib; Emad Hosseinpour (Journal of Engineering)
Composite slim floor systems are increasingly applied in the construction industry. Therefore, several experimental and numerical studies have been conducted to investigate the composite flooring systems and examine the various details that may affect the production of composite floors. This review paper summarises some important developments of composite slim floor beams, such as the type of steel beam cross section and shear connectors used, presenting essential results and important notes from various studies. The fundamental structural elements and the contribution of conducted studies towards improving the shear capacity of composite beams in enhancing the general structural behaviour were also described. Finally, the paper concludes with the potential of a deeper investigation of some issues that accompany the application of certain types of shear connects or steel shapes used to improve the composite slim floor system so that the improvement construction industry may make the most out of using composite construction techniques.